Rhabdomyolysis induced by low voltage extended electric shock in a bovine - Santos, Kaio Augusto dos; Menegatt, Jean Carlo Olivo; Lopes, Fabrício Bianco; Tineli, Tainara Renata; Tortelli, Maria Cecília Munaretto; Zimermann, Francielli Cordeiro; Ramos, Adriano Tony (Brazilian Journal of Veterinary Pathology, 2023)
Electric fences are great alternatives in the management of cattle pasture; however, they require extra attention when cherishing for the animals’ safety. Electric shocks caused by an artificial source are known as eletroplession or electrocution. Cases associated with electric fences often occur due to incorrect handling or even herd dispersion during panic. This study aims to report the epidemiological, clinical, and pathological features of prolonged electric shock in a bovine from Santa Catarina state, Brazil. The animal was found with its pelvic members stuck in the low-voltage electric fence. Twenty-four hours after the incident, the bovine showed clinical signs of apathy, depression, anorexia, and reluctance to move. In 96 hours, it was found in a lateral decubitus, with pedaling movements and nystagmus. After another 48 hours, there was no clinical improvement, and the animal was euthanized due to the unfavorable prognosis. Necropsy was performed, and fragments of all organs were collected for histopathological analysis. Gross and microscopic lesions associated with clinical signs demonstrated acute rhabdomyolysis due to electric shock, which resulted in the animal’s recumbency. Histopathological analysis also revealed neurological damage due to the electric shock. Prolonged and low-voltage electrical discharges can cause acute rhabdomyolysis in bovines. This condition should be considered with a reserved to unfavorable prognosis due to the neurological disorders and possible kidney damage.